Odpowiedzi

2009-10-13T17:28:44+02:00
Nr.1
3x=6,5-1⅚y
2y=1⅔+13x /:2

3x=6,5-1⅚y
y=⅚+6,5x

3x=6,5-11/6*(5/6+13/2x)
y=⅚+6,5x

3x=6,5-55/36+143/12x
y=⅚+6,5x

3x-11 11/12x=234/36-55/36
y=⅚+6,5x

-8 11/12x=4 25/36

-107/12x=179/36 /*12
-107x=179/3 /:(-107)
x=-179/321


3x=6,5-11/6y
2y=1⅔+13x

3x=6,5-11/6y /*13
-13x=5/3-2y /*3

39x=84,5-143/6y
-39x=5-6y
__________________
143/6y=84,5
6y=5

179/6y=89,5 /*6
179y=537 /:179
y=3
2*3=1⅔+13x
6=1 2/3+13x
13x=6-1 2/3
13x=13/3 :13
x=1/3


Nr.2
2x-9=10-0,1y
⅕x +2,5+¼y=2 /*5

2x-9-10=-0,1y
x+12,5+5/4y=10

2x-9-10=-0,1y
x=10-12,5-5/4y

2x-9-10=-0,1y
x=-5/2-5/4y

2(-5/2-5/4y)-19=-0,1y
x=-5/2-5/4y

-5-5/2y-19=-0,1y
x=-5/2-5/4y

-1/10y+25/10y=-24
x=-5/2-5/4y

2,4y=-24 /:2,4
x=-5/2-5/4y

y=-10
x=-5/2-5/4y

y=-10
x=-5/2-5/4*(-10)

y=-10
x=-5/2+25/2

y=-10
x=20/2

y=-10
x=10


2x-9=10-0,1y
1/5x +2,5+¼y=2 /*(-10)

2x-9=10-0,1y
-2x-25-2,5y= -20

-9-10= -0,1y
-25+20=2,5y

-0,1y=-19
2,5y=-5
_______
2,4y=-26 /:2,4
y=-10 10/13

2x-9=10-0,1*(-260/24)
2x=10+9+260/240
2x=20 1/12 /:2
x=241/24=10 1/24

Coś mi wyszło nie tak :( Mam nadzieję, że chociaż jakoś pomogłam.
3 3 3